Soret and Dufour Effects on Combined Sakiadis and Casson Fluid Flows Towards Horizontal Surface: A Cattaneo-Christov Heat Flux Model - Janaiah, Ch.; Reddy, G. Upender (Communications in Mathematics and Applications, 2022)
This study’s findings are Soret and Dufour Possessions upon steady, glutinous, incompressible with joint tide of Sakiadis and Casson fluids headed for horizontal surface in the ferromagnetic materials, the arise and Cattaneo-Christov warmness flux model using numerical solutions. Diffusion thermo in addition framework of thermoelastic thermal conductions are added voguish energy equation as well as thermal diffusion effect is added in concentration equation. Using similarity quantities, the fundamental governing equations are besides order to another sequence pertaining to finite difference numerical integration high not straight besides resolved used this Runge-Kutta process arithmetically based bombardment procedure. These flow variables such as, rapidity, hotness and deliberation silhouettes are discussed graphically by variations of pertinent parameters. Also, the quantities related engineering aspects like casing-abrasion, Nu numeral besides Sh numeral coefficients were also acquired but rather illustrated concluded even forms. Procured analytical results have been compared near reported writings but instead kept trendy good accord.
Keywords: Soret effect; Dufour effect; Sakiadis fluid; Casson fluid; Cattaneo-Christov heat flux